A dual-site and dual-turn-on fluorescence probe for imaging mitochondrial HClO and SO2. (January 2022) - Bao, Xiazhen; Ai, Kaili; Cao, Xuehui; Chen, Dongping; Zhou, Bo; Huo, Congde
Abstract: Bioactive small molecules, hypochlorous acid (HClO) and sulfur dioxide (SO2 ), play vital roles in the maintenance of normal physiological function of living organisms. Once their balance is interrupted, it would cause oxidative stress and various diseases. Therefore, monitoring the change of HClO and SO2 in cellular levels and in vivo is of great significant for exploring their physiological and pathological roles. Herein, we present a dual-site and dual-turn-on fluorescence probe PTBI that could simultaneously monitor HClO and SO2 in mitochondria by two well-separated emission channels with a difference of 115 nm. The probe exhibited fast response (HClO: < 5 s, SO2 : <1 min) and low detection limits with 45.8 and 53.2 nM for HClO and SO2, respectively. Using the single fluorescence molecule, we not only realized the detection of the basal and exogenous/endogenous levels of HClO and SO2, but also achieved the monitoring mitochondrial oxidative stress induced by HClO in living cells and zebrafish. Graphical abstract: Image 1 Highlights: PTBI features dual-site and dual-turn-on response to HClO and SO2 with a sufficient fluorescence signals interval. PTBI displays fast response to HClO (within 5 s) and SO2 (within 1 min). PTBI possesses excellent sensitivity towards HClO and SO2 with detection limits of 45.8 and 53.2 nM, respectively. PTBI is successfully applied to detect the basal and exogenous/endogenous levels of HClO and SO2 . PTBI is applied to monitor the mitochondrial oxidative stress induced by HClO.